The molecular landscape of premenopausal breast cancer. Issue 1 (December 2015) - Liao, Serena; Hartmaier, Ryan; McGuire, Kandace; Puhalla, Shannon; Luthra, Soumya; Chandran, Uma; Ma, Tianzhou; Bhargava, Rohit; Modugno, Francesmary; Davidson, Nancy; Benz, Steve; Lee, Adrian; et al.
Abstract Introduction Breast cancer in premenopausal women (preM) is frequently associated with worse prognosis compared to that in postmenopausal women (postM), and there is evidence that preM estrogen receptor-positive (ER+) tumors may respond poorly to endocrine therapy. There is, however, a paucity of studies characterizing molecular alterations in premenopausal tumors, a potential avenue for personalizing therapy for this group of women. Methods Using TCGA and METABRIC databases, we analyzed gene expression, copy number, methylation, somatic mutation, and reverse-phase protein array data in breast cancers from >2, 500 preM and postM women. Results PreM tumors showed unique gene expression compared to postM tumors, however, this difference was limited to ER+ tumors. ER+ preM tumors showed unique DNA methylation, copy number and somatic mutations. Integrative pathway analysis revealed that preM tumors had elevated integrin/laminin and EGFR signaling, with enrichment for upstream TGFβ-regulation. Finally, preM tumors showed three different gene expression clusters with significantly different outcomes. Conclusion Together these data suggest that ER+ preM tumors have distinct molecular characteristics compared to ER+ postM tumors, particularly with respect to integrin/laminin and EGFR signaling, which may represent therapeutic targets in this subgroup of breast cancers.